Evaluation of the Clinical Features of 81 Patients with COVID-19: An Unpredictable Disease in Children - Temel, Hayrettin; Gündüz, Mehmet; Arslan, Hüseyin; Ünal, Füsun; Atağ, Emine; Cömert, Murat; Doğan, Mehmet Sait; Erkesim, Remzi; Okur, Mesut; Öktem, Sedat; Tosun, Ayşe İstanbullu (Journal of Pediatric Infectious Diseases, 2020)
Objective Data on the prognosis of clinical features of pediatric patients affected by the coronavirus disease 2019 (COVID-19) pandemic is insufficient. This study aimed to examine the clinical, laboratory, and radiology findings of pediatric patients diagnosed with COVID-19.Methods A total of 81 pediatric patients with a confirmed diagnosis of COVID-19 who were admitted to the pediatric clinics of our tertiary care hospital in Istanbul between March 22 and May 1, 2020, were included in the study.Results Of the patients, 40 (49.6%) were boys and 41 (50.6%) were girls. The mean age of the patients was 9.3 ± 5.5 years (range: 1 month–16 years). The most common symptoms were cough (28.4%) and fever (25.9%). A total of 26 patients (32.1%) had pharyngeal erythema. There was no significant difference between age groups in terms of symptoms, findings, clinical picture, history of contact, and clinical course (p > 0.001 for each). Abnormal findings were observed in seven (8.6%) patients on chest X-ray, and in four patients (4.9%) on thorax computed tomography. Only three of the patients were hospitalized and all of them discharged with healing.Conclusion The present study is the most comprehensive study on children diagnosed with COVID-19 in our country, which showed that the COVID-19 picture was mild in pediatric patients, but the signs and symptoms in children were not specific to the disease. Our findings also showed that the rate of asymptomatic infection in children was high and that it was difficult to recognize COVID-19 in children.
Keywords: COVID-19; coronavirus; pediatric patient; Turkey